A Synchronization Structure Of SSTC And Its Applications In Machine Translation. - Al-Adhaileh, Mosler R.; Kong, Tang Enya; Yusoff, Zaharin (2002)
In this paper, a flexible annotation schema called (SSTC) is introduced. In order to describe the correspondence between different languages, we propose a variant of SSTC called synchronous SSTC (S-SSTC). We will also describe how S-SSTC provides the flexibility to treat some of the non-standard cases, which are problematic to other synchronous formalisms.